Plant cell death processes - Noodén, Larry D; Ed (Elsevier Academic Press, 2004)
Programmed cell death is a common pattern of growth and development in both animals and plants. However, programmed cell death and related processes are not as generally recognized as central to plant growth. This is changing fast and is becoming more of a focus of intensive research. This edited work will bring under one cover recent reviews of programmed cell death, apoptosis and senescence. Summaries of the myriad aspects of cell death in plants Discussion of the broadest implications of these disparite results A unification of fields where there has been no cross talk Enables easy entry into diverse but related lines of research.